Adopting Principles of Freinet Pedagogy for Research Skill Development in Higher Education - Oppl, Stefan (Momentum Quarterly, 2017)
The development of research skills in higher education curricula is considered an important component for personal and professional development. Empirical evidence shows that students’ autonomy and creativity when performing research can be effectively supported by open, work-centric learning settings. The present work builds upon these results and proposes an approach that draws from the concept of work-based learning in general and the ideas of Freinet pedagogy in particular. The article reviews the state-of-the-art in research on the deployment of Freinet pedagogy in higher education and introduces a course design on scientific work and writing practices based on Freinet principles. It discusses findings from three cycles of action research on this course in an undergraduate business information systems curriculum, and reports on its evolution over time. The results show that Freinet principles can be de-ployed in higher education, but require adaptation to account for the high workload and limited flexibility of current curricula. These findings are used to discuss potential implications for curriculum design and higher education policies.